Sekolah Rakyat during the Colonial Period: An Instrument of Colonial Control and a Space of Emancipation in the History of Indonesian Education - Risma Juniati Tambunan; Yudha Rivaldo Silalahi; Nadia Ramadhani; Muhammad Ardiansyah Rasuna; Hobblinnardo Simanullang; Arfan Diansyah (Mahesa Research Center (PT. Mahesa Global Publishing), 2025)
This article examines Sekolah Rakyat (Volksschool) within the structure of the Dutch colonial education system in Indonesia, situating it in the broader context of colonial governance and the Ethical Policy. The study addresses how Volksschool functioned simultaneously as an instrument of colonial control and as a site that generated unintended emancipatory consequences for the indigenous population. Employing historical research methods with a qualitative library approach—comprising heuristics, source criticism, interpretation, and historiography—this research analyzes colonial education regulations, curriculum documents, and statistical reports from the early twentieth century. The findings reveal that Volksschool was designed to produce a disciplined, low-skilled indigenous labor force through a restricted curriculum focused on basic literacy, numeracy, and practical knowledge. Archival data, however, indicate measurable increases in literacy rates and school participation, which facilitated access to printed media and engagement in early nationalist organizations. The study argues that while Volksschool reinforced colonial administrative structures and social stratification, it also unintentionally laid structural foundations for the growth of national consciousness and the subsequent development of Indonesia’s national education discourse.